recall...
log ( x * y ) = log x + log y
log ( x / y) = log x - log y
log ( m^n ) = n log m
use above laws of logarithms
we get
log ( a^7 / b^3 c^4) = log (a^7 ) - log ( b^3 c^4)
= 7 log a - ( log b^3 + log c^4 )
= 7 log a - ( 3 log b + 4 log c )
so final answer is 7 log a - 3 log b - 4 log c
2007-04-23 10:02:47
·
answer #1
·
answered by RAKESHtutor 3
·
0⤊
0⤋
Funny you should ask. First, the rules.
Exponents go outside the log term as multipliers.
Addition of logs corresponds to multiplication of the terms.
Subtraction of logs corresponds to division of the terms.
So...... we have 7log a - (3 log b + 4 log c).
Hope that helps!
2007-04-23 17:05:36
·
answer #2
·
answered by cattbarf 7
·
0⤊
0⤋
Ok, first we must discuss the properties of the logarithm:
First there is the division property, which says:
log(a/b) = loga - logb
Simple.
Then there is the multiplication property, which says:
log(ab) = loga + logb
Finally, there is the exponent property, which says:
log(a^n) = n(loga)
Now we look at your problem:
log(a^7/(b^3c^4))
Division Property:
log(a^7) - log(b^3c^4)
Multiplication Property:
log(a^7) - log(b^3) + log(c^4)
Exponent Property:
7log(a) - 3log(b) + 4log(c)
And there you go.
2007-04-23 17:06:58
·
answer #3
·
answered by Eolian 4
·
0⤊
1⤋
log(a^7/(b^3c^4) = log(a^7) - log(b^3c^4)
= log(a^7) - log(b^3) - log(c^4)
=7log(a) - 3log(b) - 4log(c)
2007-04-23 17:04:28
·
answer #4
·
answered by Mαtt 6
·
0⤊
0⤋
assuming you mean log[(a^7)/(b^3c^4)]:
apply the properties of logs:
log(xy)= log(x)+ log(y)
log(x/y)= log(x) - log(y)
log(x^y)= ylog(x)
therefore...
log(a^7) - [log(b^3) + log(c^4)]
7log(a) - [3log(b) + 4log(c)] or
7log(a) - 3log(b) - 4log(c)
2007-04-23 17:05:34
·
answer #5
·
answered by blackcat3556 4
·
0⤊
0⤋
7loga - 3logb + 4logc
2007-04-23 17:03:42
·
answer #6
·
answered by ktraver15 2
·
0⤊
0⤋
7loga -(3logb + 4logc)
2007-04-23 17:12:33
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
7loga-(3logb+4logc)
2007-04-23 17:03:34
·
answer #8
·
answered by ... 2
·
0⤊
0⤋